Gender, Family Help, and Homework Management Reported by Rural Middle School Students - Jianzhong Xu (Journal of Research in Rural Education, 2006)
This study linked gender, family help, and grade level to 5 features of homework management reported by 238 rural middle school students. The 5 features studied were setting an appropriate work environment; managing time; and controlling attention, motivation, and potentially interfering emotions. No significant differences were found across grade levels on any of the 5 homework management indices. Compared with boys, girls reported more frequently working to budget time, to be self-motivating during homework, and to control potentially interfering emotions. Students who received family help, compared to those who did not, reported more frequently working to manage their workspace, to be self-motivating during homework, and to control potentially interfering emotions. The article discusses these findings in the context of recent theoretical frameworks and empirical studies. In addition, it suggests directions for future research and practice related to homework management for rural middle school students.